Pengaruh Lingkungan Kerja Dan Skill Terhadap Kinerja Pramuniaga Yang Bekerja Di Mall - B.L, Avni Tinansia (CV. ITTC INDONESIA, 2024)
This research aims to analyze the influence of the work environment and skills on the performance of sales assistants working in malls. A conducive work environment and adequate skills are important factors that can influence the productivity and efficiency of salespeople. The research method used is qualitative with a literature approach. Data was collected through various literature such as journals, articles and books. The research results show that a good work environment and high skills significantly influence the performance of sales assistants. A comfortable, safe and supportive work environment can improve salesperson performance. Meanwhile, skills that are relevant to the duties and responsibilities of sales assistants have also been proven to increase efficiency and service quality. These findings indicate the importance of mall management to create a positive work environment and provide the necessary training to improve salesperson skills, thereby improving overall performance and customer satisfaction